PELITAH: ZERO WASTE COFFEE PRODUCTION FOR SUSTAINABLE DEVELOPMENT OF WANAKA COFFEE CULTIVATION THROUGH SOCIAL EMPOWERMENT - Ibnu Agus Santosa; Eva Wirabuana; Muhammad Ali Sabbit Zamzani; Yunara; Dito Hastha Krisandy; Ahsani Paramitasari; Rifky Taufiq Fardian; Reza Rahman Ramadhan (Globalwriting Academica Consulting & Publishing, 2022)
This study aims to analyze PELITAH Waste Coffee Production for Sustainable Development of Wanaka Coffee Cultivation through Social Empowerment. This research uses qualitative research with descriptive analysis approach. The types of data in this study consist of primary data and secondary data, primary data obtained from research respondents and secondary data obtained from literature studies. The collected data is presented using qualitative methods. PELITAH already changed people's behavior at the system level. This change community awareness in waste management. Through the processing of some of these derivative products, all coffee skin waste in every season are processed out by community. So there are no coffee skin waste burned by the community. The environment has changed and indirectly community's waste behavior improving the economy also maintains environmental sustainability.